No Place for Wimps: Working on Western Australian Trawlers - Stella, Leonie (Anthropologica, 2022)
This article is part of a larger project, undertaken as a doctoral thesis, analyzing gender relations in the Western Australian fishing industry. The article is based on qualitative research and the primary focus is the sexual division of labour on prawn and scallop trawlers. Few women own or operate boats or companies and I argue that the trawler, as a worksite, is dominated by a competitive and aggressive heterosexual masculinity that sustains an inequitable division of labour